The Indian Civil Service and Indian Foreign Policy, 1923-1961 - Das Gupta, Amit; Das Gupta, Amit (Taylor & Francis Routledge [Imprint], 2020)
Nehruvian Diplomacy, Indian diplomacy, Cold War politics, decolonisation, British India, World War II, Gandhi
eng
Keywords: Civil service -- India -- History -- 20th century; Civil service; Diplomatic relations; History and Archaeology; History: specific events and topics; History; National liberation and independence; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / General; Politics and government; Public administration; SOCIAL SCIENCE / General; Society and Social Sciences; British India; Cold War politics; decolonisation; Gandhi; Indian diplomacy; Nehruvian Diplomacy; World War II